60 Post Inpatient Fall Medical Assessment (PIFMA) Performa Quality Improvement Project. (6th February 2020) - Chan, M; Tan, C W; Mathew, P
Abstract: Introduction: Inpatient falls are the most commonly reported patient safety incidents and in the United Kingdom, there are 250, 000 reported falls per year 1. A rapid response report (RRR) issued in 2011 by the NPSA highlighted need for improvement in identifying fractures and neurological observations. These figures reflect significant implications to patients' health and financial burden to the NHS. Aims: To improve assessment and documentation of inpatient falls assessment. Methods: Two PDSA cycles were completed. First PDSA cycle established a baseline of post fall assessment and documentation in which raising awareness and teaching (RAT) to junior doctors was done. Second PDSA cycle identified room for further improvement and post inpatient fall medical assessment (PIFMA) Performa was developed to aid assessment and documentation for use of junior doctors. Feedback regarding the usefulness of the PIFMA Performa was collected via survey. Results: The RAT intervention involved 30 patients of the Elderly wards in November and December 2017 and the PIFMA intervention involved 29 patients in all Medical wards in January and February 2019. The PIFMA Performa improved the time taken to review patients as per doctors survey. On comparing the RAT against PIFMA Performa interventions, documentation improved in the categories of physical examination (from 80% to 97%), neurological observations (from 49% to 98%), medication review (from 53% to 83%), and measuring lying standing blood pressure (from 83% to 90%). Conclusions: Feedback from junior doctors states that the PIFMA Performa was certainly a very useful guidance tool and help to speed up documentation. These improvements only translated if junior doctors utilize the PIFMA Performa and so this is now being implemented in the trust policy. Further PDSA cycle can reassess if improvements truly represent the population cross-section. References: 1. The incidence and costs of inpatient falls in hospitals (2017), NHS improvement. 2. National Patient Safety Agency NPSA/2011/RRR001 (13 January 2011).